Europeanising spaces in Paris, c. 1947-1962 - McDonnell, Hugh (Liverpool University Press, 2016)
"In the wake of the Second World War, ideas of Europe abounded. What did Europe mean as a concept, and what did it mean to be European? Europeanising Spaces in Paris, c. 1947-1962 makes the case that Paris was both a leading and distinctive forum for the expression of these ideas in the post-war period. It examines spaces in the French capital in which ideas about Europe were formulated, articulated, exchanged, circulated, and contested during this post-war period, roughly between the escalation of the Cold War and the end of France's war of decolonisation in Algeria. Such processes of making sense of Europe are elucidated in urban, political and cultural spaces in the French capital. Specifically, the Parisian cafe, home and street are each examined in terms of how they were implicated in ideas about Europe. Then, the Paris-based Mouvement socialiste des etats unis d'Europe (The Socialist Movement for the United States of Europe) and the far-right wing Federation des etudiants nationalistes (The Federation of Nationalist Students) are examined as examples of political movements that mobilised around--very different--concepts of Europe. The final section on cultural Europeanising spaces draws attention to the specificities of the Europeanism of exiles from Franco's Spain in Paris; the work of the great scholar of the Arab world, Jacques Berque, in the context of his understanding of the Mediterranean world and his understanding of faith; and finally, the work of the legendary photographer, Henri Cartier-Bresson, by looking at the capacities and limitations of the photographic medium for the representation of Europe, and how these corresponded with Cartier-Bresson's political, social, and aesthetic commitments"--Publisher description.